GLI inhibitor GANT61 kills melanoma cells and acts in synergy with obatoclax - Vlčková, Kateřina; Réda, Jiri; Ondrušová, Lubica; Krayem, Mohammad; Ghanem, Ghanem; Vachtenheim, Jiri (International journal of oncology, 2016)
MEK kinase inhibitors (trametinib and selumetinib) or kinase inhibitors directed against mutated BRAF(V600E) (vemurafenib and dabrafenib) have initial encouraging effects in the treatment of melanoma but acquired resistance appears almost invariably after some months. Studies revealed mutually exclusive NRAS and BRAF activating mutations driving the MAPK/ERK pathway among human melanomas. Although combination therapy exerts significantly better antitumor cell efficacy, complete remission is rarely achieved. To employ an alternative approach, we have targeted the Hedgehog/GLI pathway, which is deregulated in melanomas, through the GLI1/2 inhibitor GANT61, alone or accompanied with the treatment by the BCL2 family inhibitor obatoclax in 9 melanoma cell lines. Thus, we targeted melanoma cells irrespective of their NRAS or BRAF mutational status. After GANT61 treatment, the cell viability was drastically diminished via apoptosis, as substantial nuclear DNA fragmentation was detected. In all tested melanoma cell lines, the combined treatment was more efficient than the application of each drug alone at the end of the cell growth with inhibitors. GANT61 was efficient also alone in most cell lines without the addition of obatoclax, which had only a limited effect when used as a single drug. In most cell lines, tumor cells were eradicated after 5-9 days of combined treatment in colony outgrowth assay. To conclude, GANT61 treatment might become a hopeful and effective anti-melanoma targeted therapy, especially when combined with the BCL2 family inhibitor obatoclax.
Keywords: Cell Survival; Membrane Proteins; indoly; Kruppel-Like Transcription Factors; Humans; Indoles; pyrimidiny; Proto-Oncogene Proteins B-raf; melanom; protein Gli2 s motivem zinkových prstů; mutace; Drug Synergism; Antineoplastic Agents; pyrroly; jaderné proteiny; lidé; proliferace buněk; Pyridines; synergismus léků; Pyrroles; protoonkogenní proteiny B-Raf; GTP-fosfohydrolasy; Melanoma; Cell Proliferation; Nuclear Proteins; transkripční faktory Krüppel-like; pyridiny; nádorové buněčné linie; protinádorové látky; membránové proteiny; Zinc Finger Protein Gli2; Cell Line, Tumor; Mutation; Pyrimidines; viabilita buněk; GTP Phosphohydrolases